Transforming legal education through emotions. (31st July 2018) - Jones, Emma
Abstract: Law has traditionally viewed emotions as the enemies of rationality and reason, irrational and potentially dangerous forces which must be suppressed or disregarded. This separation and enmity has been mirrored within undergraduate legal education in England and Wales, with its rigid focus on seemingly impartial and objective analysis and notions such as the ubiquitous 'thinking like a lawyer'. This paper will argue that attempts to disregard or suppress emotions within the law school are both misguided and destined to fail. It will explore the integral part emotions play within effective legal learning, the development of legal skills, and the well-being of both law students and legal academics. It will also consider how developments in legal scholarship and the evolving climate of higher education generally offer some potential, but also pitfalls, for the future acknowledgment and incorporation of emotions within undergraduate legal education in England and Wales. Bodies of literature relating to not only legal education, but also education generally, psychology and philosophy will be drawn on to demonstrate that emotions have a potentially transformative power within legal education, requiring them to be acknowledged and utilised within a more holistic, integrated form of law degree.